ANALISIS DRAMATURGI TERHADAP PRAKTIK IMPRESSION MANAGEMENT FRESH GRADUATE DI MEDIA SOSIAL LINKEDIN - Fakhirah, Nadia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasingly competitive labor market encourages fresh graduates to develop strategies for managing their professional identity, one of which is through the utilization of LinkedIn as a professional social media platform. LinkedIn not only functions as a job-search platform but also serves as a digital performance space where individuals engage in impression management practices before professional audiences. This study aims to examine the impression management practices of fresh graduates on LinkedIn through Erving Goffman’s dramaturgical perspective. This study employs a qualitative approach with a case study method. Data were collected through online observation, in-depth interviews, and documentation of informants’ LinkedIn profiles and activities, selected using purposive sampling. The findings reveal that fresh graduates’ impression management practices occur through a dynamic relationship between the front stage and backstage. The backstage functions as a preparation space where actors conduct research, evaluation, information arrangement, and selection before presenting themselves on the front stage. Meanwhile, responses from professional audiences toward front-stage performances become feedback that encourages actors to evaluate and renegotiate the professional identity they present. On the front stage, LinkedIn functions as a digital setting where actors construct their personal front through appearance and manner, involving the management of displayed attributes, professional information, and ways of communicating their competencies. This study identifies two patterns of professional self-presentation: a formal-professional pattern that emphasizes competencies and achievements, and an authentic-personal pattern that combines professional identity with personal characteristics. Thus, fresh graduates’ impression management on LinkedIn represents a dramaturgical process that continuously occurs through a cycle of preparation, performance, audience response, and further adjustment of the presented professional identity.